Pengaruh Lokasi, Kualitas Pelayanan Dan Kepercayaan Pelanggan Terhadap Kepuasan Pelanggan Dalam Jasa Pengiriman Anteraja - Mevi Permata Sari; Nur Hidayati; Nurali Agus Najibul Zamzam (Politeknik Kampar, 2023)
The problem that is the focus of this study is the problem of location variables (X1), service quality (X2) and customer trust (X3) to the dependent variable, namely customer satisfaction (Y). The customer population of PT Tri Adi Bersama (ANTERAJA) is 7300 people. This research uses quantitative methods. Sampling technique with purposive sampling approach. The data analysis technique used in this research is validity and reliability test, classic assumption test, multiple linear regression test, coefficient of determination, t test and F test. From the results of this study that the location variable (X1) has a partially significant effect on customer satisfaction (Y), this can be seen from the significant t value of 0.005 <0.05. service quality (X2) has a partially significant effect on customer satisfaction (Y), this can be seen from the significant t value of 0.005 <0.05. customer trust (X3) has a partially significant effect on customer satisfaction (Y), this can be seen from the significant t value of 0.029 <0.05. Simultaneously location (X1), service quality (X2) and customer trust (X3) have a significant influence on customer satisfaction (Y), this can be seen from the significant F value of 0.000 <0.05.